THE EFFECTIVENESS OF USING LEARNING JOURNALS ASSESSED FROM LEARNING OUTCOMES AND METACOGNITIVE ABILITY IN PAI LEARNING - Syafruddin Syafruddin; Hamdanah Hamdanah; Ahdar Ahdar; Zulfah Zulfah; Muzakkir Muzakkir (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effectiveness of the use of study journals assessed from students' abilities and students' metacognition abilities in solving Al-Qur'an Hadith problems at SMKN 1 Barru. The method in this study is an experiment involving learning using a study journal. The sample in this study were all 12 students of class XI. The sampling technique in this study is saturated sampling. The use of study journals is less effective in terms of students' abilities in solving problems with the Qur'an Hadith system, this can be shown by the percentage of students who complete, namely only 50% of the total students get learning outcomes of ≥70, ≥66.67%.